Protective role of Urtica dioica L. (Urticaceae) extract on hepatocytes morphometric changes in STZ diabetic Wistar rats - Mohammad Jafar GOLALIPOUR,; Soraya GHAFARI,; Mohammad AFSHAR, (Turkish Journal of Gastroenterology, 2019)
-